Give the farmer access - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The article in Spore 80 entitled 'Poverty Reduction: Simply a Question of Access?' prompted a thundering 'YES!' from S.O Obenjo of Gbensola Enterprises in Osogbo, Osun State, Nigeria. Talking of his need to stockpile his cassava crop until prices...